2006
DOI: 10.1111/j.1468-3148.2006.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Offences in Police Reports and Court Dossiers: A Case‐File Study

Abstract: Background  In many cases, sexual abuse involving a person with an intellectual disability (ID; as a victim and/or as a perpetrator) is not reported to the police. There are very few studies addressing police procedures in these cases, and even fewer addressing procedures at the Public Prosecutor level. The present study had two goals: (i) to describe relevant characteristics of cases of sexual abuse, involving people with ID (as a victim or perpetrator), that were either reported to the police or sent to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
2
4
0
Order By: Relevance
“…In general, the findings reveal that the majority of victims were female in their early twenties and were victims of sexual abuse perpetrated by someone they knew. These findings are similar to those of other studies in the field; Van Den Bergh and Hoekman (2006) found that the majority of victims in their study were female in their twenties who were alleged victims of sexual abuse. PWID's vulnerability to being sexually exploited regardless of gender was also reported by Nixon et al (2017).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In general, the findings reveal that the majority of victims were female in their early twenties and were victims of sexual abuse perpetrated by someone they knew. These findings are similar to those of other studies in the field; Van Den Bergh and Hoekman (2006) found that the majority of victims in their study were female in their twenties who were alleged victims of sexual abuse. PWID's vulnerability to being sexually exploited regardless of gender was also reported by Nixon et al (2017).…”
Section: Discussionsupporting
confidence: 91%
“…Studies have furthermore compared questioning strategies used for children and concluded that these are recommendable for PWID and PWA regardless of age (Lamb et al 2018b). There are more criminal cases within the criminal justice system that involve adult than child victims with disabilities (Van Den Bergh and Hoekman 2006;Nixon et al 2017). We therefore require more knowledge of how adults with disabilities are questioned in investigative interviews.…”
Section: Discussionmentioning
confidence: 99%
“…Similar findings were reported in studies that analyse the relationship between victim and suspect. For example, a Dutch study conducted by Van Den Bergh and Hoekman () reports two‐fifths of suspects being a friend or acquaintance. A study from the United States also reports that someone the victim knew well conducted 40% of crimes against people with intellectual disabilities (Harrell, ).…”
Section: Discussionmentioning
confidence: 99%
“…The call for more research about the judicial process involving victims with disabilities is still applicable, but access to information within the criminal justice system has repeatedly been discussed as a reason for the lack of studies within this area (Cederborg & Lamb, ; Fry, Lannen, Vanderminden, Cameron, & Casey, ; Hughes et al, ; Jones et al, ; Murphy et al, ; Olafson, ). The limited access to information can lead to methodological challenges such as described in a study conducted by Van Den Bergh and Hoekman (). In their study, where the aim was to describe the judicial process in sexual offence cases, the sampling procedure was dependent on a manual screening of files.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation